DEVELOPMENT AND IMPLEMENTATION OF SURGICAL METHODS FOR THE TREATMENT OF STENOSIS OF THE SUBGLOTTIC LARYNX (Conferencea, 2023)
The objective of the present study was to optimize the treatment of patients with subglottic laryngeal stenosis.